Penguatan Sikap Kejujuran dan Tolong-Menolong Melalui Drama Enam Penyihir Penyelamatan Hutan di TK Bakti 2 Ngesrep Boyolali - Azizah, Annafi’ Nurul ‘Ilmi; Alifvia, Pinkan Tradya; Ananda, Afifah Fadhilah Surya; Rofi’ah, Anisatur; Salabila, Fatwa Naila; Nisa, Destria Choirun; Fajriati, Nurvita (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service initiative addresses the critical need for robust character education in early childhood, specifically fostering honesty and helping attitudes through an innovative drama performance titled "Six Witches Rescuing the Forest". Recognizing the pivotal role of formative years for personality and moral development, and the common underdevelopment of crucial values like honesty and compassion, drama was meticulously chosen. Its interactive and imaginative nature allows for seamless integration of value-based learning with profound emotional experiences, ensuring moral messages are conveyed enjoyably and deeply internalized. The multi-stage methodology involved thorough preparation, initial observations to identify children's needs, an engaging drama performance, and comprehensive evaluation. Conducted at TK Bakti 2 Ngesrep Boyolali with 38 children aged 4-6 years, empirical findings indicate significant improvement in children's interaction abilities, appropriate emotional expression, and internalization of honesty and helping values. This demonstrates role-playing drama as a powerful pedagogical tool for positive character building and strengthening social relationships, preparing children to be responsible and empathetic individuals for future societal contributions.